Oxidative stress biomarkers in newborn calves: Comparison among artificial insemination, in vitro fertilization and cloning - Dantas, Gabriela N. [UNESP]; Santarosa, Bianca P. [UNESP]; Santos, Vitor H.; Hooper, Henrique B.; Micai, Ricardo A.; Sinzato, Yuri K. [UNESP]; Damasceno, Débora C. [UNESP]; da Silva, Andreza A.; Benesi, Fernando J.; Gonçalves, Roberto C. [UNESP] (Elsevier, 2020)
Oxidative stress occurs when there is greater than optimal production of reactive oxygen species (ROS) or an antioxidant system failure. Calves produced using in vitro fertilization (IVF) or cloning (CA) have greater mortality rates, with greater incidence of respiratory diseases, which could be explained by the deleterious outcomes from oxidative stress. Calves were studied that were produced using: artificial insemination (AI; n = 20), in vitro fertilization (IVF; n = 15) or cloning (CA; n = 15). Blood samples were collected at 6, 12, 24 and 48 h subsequent to the time of birth. The cloned calves had greater ROS production from lipid peroxidation, with greater thiobarbituric acid reactive substances. This factor was associated with a lesser amount of superoxide dismutase in the CA. Calves produced using IVF had a greater activity of catalase and glutathione peroxidase, either due to greater production of hydrogen peroxide or greater efficiency of enzymatic response of these neonates. Calves produced using AI had greater concentrations ​​of reduced thiol groups. These associated factors may indicate there is greater oxidative stress in calves produced by IVF and cloning than with use of AI, however in these calves there was an effective response to these oxidative stressors within 48 h subsequent to birth. Hence, calves produced using IVF and by cloning have greater ROS production when compared to calves produced using AI. The calves produced using IVF, however, had a greater enzymatic activity or were more efficient in adapting to ROS when compared to calves produced by cloning.
Keywords: Antioxidant enzymes; Cattle; Lipid peroxidation; Neonatology; Reactive oxygen species